Measuring the intensity of smoking behavior among beneficiaries of subsidized health insurance: Item Response Theory (IRT) Analysis - maulida, rizki wibias anwar; Nasrudin, Rus'an (Universitas Negeri Semarang, 2024)
The absence of sufficient income leaves the impoverished and near-poor particularly susceptible to economic shocks, yet they encounter significant barriers in accessing the health insurance market. The government introduced the Health Premium Assistance for the Poor and Near-Poor (Askeskin) program on January 1, 2005, to address this issue. However, individuals with lower socioeconomic status are disproportionately likely to smoke. Therefore, it is imperative to conduct screening and assess smoking intensity, particularly among those facing economic hardships, to effectively address smoking behavior. To assess the severity of smoking habits among beneficiaries of subsidized health insurance (Askeskin), this study utilized data from the IFLS survey and applied Item Response Theory (IRT). IRT facilitates the development of highly precise measurement tools that accurately capture variations in an individual's health and well-being. The findings indicate that this scale serves as a suitable instrument for examining heavy smoking intensity in research endeavors, particularly within the Indonesian context.